28+3x-2=6x

Simple and best practice solution for 28+3x-2=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 28+3x-2=6x equation:


Simplifying
28 + 3x + -2 = 6x

Reorder the terms:
28 + -2 + 3x = 6x

Combine like terms: 28 + -2 = 26
26 + 3x = 6x

Solving
26 + 3x = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
26 + 3x + -6x = 6x + -6x

Combine like terms: 3x + -6x = -3x
26 + -3x = 6x + -6x

Combine like terms: 6x + -6x = 0
26 + -3x = 0

Add '-26' to each side of the equation.
26 + -26 + -3x = 0 + -26

Combine like terms: 26 + -26 = 0
0 + -3x = 0 + -26
-3x = 0 + -26

Combine like terms: 0 + -26 = -26
-3x = -26

Divide each side by '-3'.
x = 8.666666667

Simplifying
x = 8.666666667

See similar equations:

| 4x=2+4x | | 2x-6x=14 | | 2x^2-12x-6=0 | | 7e^5t=10 | | -4x^2=-5x+3 | | 5n^2-5n-30=0 | | y*.16=651 | | 2(5x-3)-x=3(3x-2) | | 2x^2+12x-108=0 | | 4*lx+8l=20 | | 90=6(-3+r) | | x^2+4xy-32y^2= | | 2x^2-80=55-x^2 | | 5x+3x=-16 | | 7x^2-65x+18=0 | | (18x^4)-(3x^2)-1=0 | | 20*20= | | 3(2x-5)=6(4-2x)-9x | | 3d+3=-d-30-7d | | x^7+7x^6-8x^5= | | u^2+9u=0 | | 50x*20=987 | | -9v+-5v=40 | | 343m^3-64n^3=0 | | (18u^2)-3u-1=0 | | 4b-12=-b+51 | | 4x^3-12x^2+8x-24=0 | | 3n^2+9n-30=0 | | P=s+bq | | 0.6(x-1)=2(0.2+0.1) | | 11*11+121/11-11= | | 7-(1-4p)=7p-3(6p-7) |

Equations solver categories